Targeted delivery of CXCR4-siRNA by scFv for HER2+ breast cancer therapy. (August 2015) - Jiang, Kuo; Li, Jia; Yin, Jipeng; Ma, Qiong; Yan, Bo; Zhang, Xiang; Wang, Lei; Wang, Lifeng; Liu, Tao; Zhang, Yinglong; Fan, Qingyu; Yang, Angang; et al.
Abstract: Therapeutics based on short interfering RNAs (siRNAs) have great potential to treat human diseases. However, the clinical application of siRNAs has been limited by their poor intracellular uptake, low serum stability, and inability to target specific cells. In this study, we addressed this lack of specificity by synthesizing a molecularly targeted CXCR4-siRNA (CXCR4si) for the treatment of HER2 + breast cancers using a HER2-scFv-arginine nonamer peptide fusion protein (e23sFv-9R) as an siRNA carrier. The e23sFv-9R binding siRNA is able to specifically deliver the siRNA to HER2 + breast cancer cells and concentrate and persist in orthotopic HER2 + breast cancer xenografts for at least 36 h. CXCR4si delivered by e23sFv-9R inhibited CXCR4 gene expression, reduced proliferation and metastasis and induced apoptosis in the HER2 + breast cancer BT-474 cell line in vitro . Moreover, the systemic delivery of CXCR4si by e23sFv-9R is able to suppress tumor growth, reduce metastasis and prolong survival in mice bearing HER2 + xenografts. This approach causes no systemic toxicity and does not activate the innate immune response, suggesting that a fusion protein carrying CXCR4si shows promise in the treatment of HER2-overexpressing breast cancer.